2011
DOI: 10.1104/pp.110.170225
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Transcriptomic Phenotyping of Inorganic Carbon Acclimation in the Cyanobacterium Synechococcus elongatus PCC 7942  

Abstract: The amount of inorganic carbon is one of the main limiting environmental factors for photosynthetic organisms such as cyanobacteria. Using Synechococcus elongatus PCC 7942, we characterized metabolic and transcriptomic changes in cells that had been shifted from high to low CO 2 levels. Metabolic phenotyping indicated an activation of glycolysis, the oxidative pentose phosphate cycle, and glycolate metabolism at lowered CO 2 levels. The metabolic changes coincided with a general reprogramming of gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
118
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(136 citation statements)
references
References 51 publications
(93 reference statements)
15
118
1
1
Order By: Relevance
“…CcmR can regulate transcription of several C i uptake genes. In Synechocystis PCC 6803, CcmR appeared to be a repressor of sbtA and the high-affinity CO 2 uptake operon but not of bicA (29,47). In contrast, in Synechococcus PCC 7002, CcmR appeared to be a repressor of bicA and sbtA and possibly the high-affinity CO 2 uptake operon (48,50).…”
Section: Evaluation Of Hypothesesmentioning
confidence: 74%
See 2 more Smart Citations
“…CcmR can regulate transcription of several C i uptake genes. In Synechocystis PCC 6803, CcmR appeared to be a repressor of sbtA and the high-affinity CO 2 uptake operon but not of bicA (29,47). In contrast, in Synechococcus PCC 7002, CcmR appeared to be a repressor of bicA and sbtA and possibly the high-affinity CO 2 uptake operon (48,50).…”
Section: Evaluation Of Hypothesesmentioning
confidence: 74%
“…Previously, the CCM genes of the model cyanobacteria Synechocystis PCC 6803, Synechococcus PCC 7002, and Synechococcus 7942 were studied in detail (15,19,(27)(28)(29)(30)(44)(45)(46)(47)(48). Comparison of the CCM genes of our Microcystis strains with these model cyanobacteria reveals several similarities and differences (Tables 2 and 3).…”
Section: Evaluation Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the two S. elongatus CP12 proteins, CP12-C and CP12-N/C, in addition to differences in potential interaction with GAPDH (Fig. 5) show differences in overall expression under constant light and in response to a shift from high to low atmospheric CO 2 (Schwarz et al, 2011;Vijayan et al, 2011). In Synechocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…MC1 and MC2 also contain a number of benzoate compounds that have been detected previously in cyanobacteria, including benzoic acid and 4-hydroxybenzoate (4HB) (Fig. S4 and Dataset S2) (38). Recent work has shown that plastoquinone biosynthesis in cyanobacteria uses 4HB as an intermediate (39,40).…”
Section: Correlations In Metabolite Abundance Can Help Classify Unknownmentioning
confidence: 99%